Differential regulation of the α-globin locus by Krüppel-like factor 3 in erythroid and non-erythroid cells - Funnell, A; Vernimmen, D; Lim, W; Mak, K; Wienert, B; Martyn, G; Artuz, C; Burdach, J; Quinlan, K; Higgs, D; Whitelaw, E; Pearson, R; et al. (BioMed Central, 2014)
Background: Krüppel-like Factor 3 (KLF3) is a broadly expressed zinc-finger transcriptional repressor with diverse biological roles. During erythropoiesis, KLF3 acts as a feedback repressor of a set of genes that are activated by Krüppel-like Factor 1 (KLF1). Noting that KLF1 binds α-globin gene regulatory sequences during erythroid maturation, we sought to determine whether KLF3 also interacts with the α-globin locus to regulate transcription. Results: We found that expression of a human transgenic α-globin reporter gene is markedly up-regulated in fetal and adult erythroid cells of Klf3−/− mice. Inspection of the mouse and human α-globin promoters revealed a number of canonical KLF-binding sites, and indeed, KLF3 was shown to bind to these regions both in vitro and in vivo. Despite these observations, we did not detect an increase in endogenous murine α-globin expression in Klf3−/− erythroid tissue. However, examination of murine embryonic fibroblasts lacking KLF3 revealed significant de-repression of α-globin gene expression. This suggests that KLF3 may contribute to the silencing of the α-globin locus in non-erythroid tissue. Moreover, ChIP-Seq analysis of murine fibroblasts demonstrated that across the locus, KLF3 does not occupy the promoter regions of the α-globin genes in these cells, but rather, binds to upstream, DNase hypersensitive regulatory regions. Conclusions: These findings reveal that the occupancy profile of KLF3 at the α-globin locus differs in erythroid and non-erythroid cells. In erythroid cells, KLF3 primarily binds to the promoters of the adult α-globin genes, but appears dispensable for normal transcriptional regulation. In non-erythroid cells, KLF3 distinctly binds to the HS-12 and HS-26 elements and plays a non-redundant, albeit modest, role in the silencing of α-globin expression.